Juridical Analysis Of The Supreme Court Jurisprudence In Insurance Company Bankruptcy Law Reviewed From Law Number 37 Of 2004 - Urrahman, M. Taopiq; Fajri, Ibrahim; Mustika, Desty Anggie (JURNAL MAHASISWA YUSTISI, 2024)
This research aims to conduct a juridical analysis of the Supreme Court's jurisprudence in the context of insurance company bankruptcy law regulated by Law Number 37 of 2004. This research explores an in-depth understanding of Supreme Court decisions relating to insurance company bankruptcy cases, with a focus on legal aspects expressed in the jurisprudence. The research method used involves document analysis, especially Supreme Court decisions, as well as a juridical approach to identify and analyze key aspects in the context of insurance company bankruptcy law. It is hoped that the results of this analysis will provide a better understanding of the interpretation of the law by the Supreme Court and its impact on the handling of insurance company bankruptcy cases. It is hoped that the findings from this research can contribute to the development and understanding of insurance company bankruptcy law in Indonesia. Apart from that, this research can also be a basis for further discussion about improving or perfecting legal regulations related to insurance company bankruptcy to ensure the protection of the interests of all parties involved in the bankruptcy process